3′-Pyrene-modified unlocked nucleic acids: synthesis, fluorescence properties and a surprising stabilization effect on duplexes and triplexes. Issue 9 (17th February 2017) - Ejlersen, Maria; Langkjær, Niels; Wengel, Jesper
Abstract : Synthesis of a novel 3′-pyrene-functionalized UNA monomer with unprecedented thermal stabilization of duplexes and triplexes. Abstract : Efficient synthesis of a new 3′- O -amino-UNA monomer was developed as a scaffold for further functionalization and incorporation into oligonucleotides (ONs). Pyrene-functionalized 3′- O -amino-UNA was incorporated one, two or three times into 21-mer DNA and 2′- O -Me-RNA ONs. Duplex melting temperatures, circular dichroism (CD) spectra, steady-state fluorescence emission spectra, UV/Vis absorption spectra and triplex melting temperatures were measured for the modified duplexes. The presence of the pyrene-modified UNA monomer lead to a surprising and unprecedented thermal stabilization of especially DNA:DNA duplexes when compared to the corresponding unmodified DNA:DNA duplexes. Improved mismatch discrimination was also seen for some of the modified duplexes. CD spectra revealed no major differences between modified and unmodified duplexes. Molecular modeling showed that the pyrene moieties were located in the minor groove of DNA:DNA duplexes as confirmed by CD and UV/Vis absorption studies. Upon multiple incorporations of the monomer in single-stranded ONs, steady-state fluorescence emission studies revealed the formation of a pyrene excimer which in most cases was quenched upon duplex hybridization, and fluorescence-based detection of mismatched hybridization was observed for some modified strand constitutions. Incorporation of the monomer in a triplex-forming oligonucleotide (TFO) strand lead to an increase of triplex melting temperature both at pH 6.0 and pH 7.0 for parallel triplexes – again an effect that has not been reported earlier for UNA-containing ONs. Steady-state fluorescence emission studies revealed significant differences in fluorescence for single-stranded ONs and triplexes.